The Effect of Socioscientific Topics on Discourse within an Online Game Designed to Engage Middle School Students in Scientific Argumentation - Jana Craig-Hare; Marilyn Ault; Amber Rowland (Journal of Education in Science, Environment and Health)
The purpose of this study was to investigate the types of argumentation discourse displayed by students when they engaged in chat as part of an online multiplayer game about both socioscientific and scientific topics. Specifically, this study analyzed discourse episodes created by middle school students as they discussed scientific and socioscientific topics within an online, multiplayer game. Using a Discourse Analysis Scoring Guide, student discussions were coded based on the type of interaction or statements made. Analysis included a comparison between the types of topics (scientific vs. socioscientific) and the student author’s justification for their decision to accept, reject or withhold judgement about the claim; teammate comments related to the author’s justification; an overall rating of the discourse episode interaction; and frequency of argumentation vocabulary use throughout the discourse episode. Results indicated that socioscientific topics produced collaborative discourse episodes that were positive, supportive, and civil within an argumentation framework.